PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS EKONOMI - Rumiyatun, Rumiyatun (Fakultas Ekonomi, Universitas Negeri Semarang, 2012)
It was a classroom action research conducted at the 1st semester of 7th Grade studentsrs of E Class in SMP Negeri 9 Semarang. It conducted since studentsâ learning outcomes on economics subject was low. Based on the initial test analysis, it can be seen that mostly IPS Economics studentsâ scores were below the minimum completeness criteria (KKM), it was 78. Thus, this study wanted to increase studentsâ learning outcomes by using jigsaw method. The subjects of the research were 33 students; 13 male students and 20 female students. The study conducted in two cycles. The results showed that Jigsaw cooperative learning model was influenceive to increase studentsâ learning outcomes. Therefore, it is suggested for teachers to use jigsaw cooperative learning model in teaching integrated social studies, and also to make good preparation and manage the time before applying this learning model.